Implementasi Pendekatan TaRL untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas IX SMPN 23 Medan : Penelitian - Yossie Camelia Sari Br Tarigan; Sinta Dameria Simanjuntak (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Thought for a second This study aims to describe the improvement in ninth-grade students’ mathematics learning outcomes at SMP Negeri 23 Medan following the implementation of the Teaching at the Right Level (TaRL) approach. The research employed a classroom action research design, with the subjects being students of class IX-B at SMP Negeri 23 Medan during the second semester of the 2024/2025 academic year. The research instrument used was a series of formative assessments. Data were collected through four phases: planning, action, observation, and reflection. Data analysis was conducted using a descriptive quantitative approach: first, student scores were tabulated and their classical completeness percentages calculated; scores meeting the school’s minimum completeness criterion (KKM) of 75 were considered to have reached mastery. The results showed that in Cycle I, 53.57% of students achieved mastery, which then increased to 82.1% in Cycle II. Since the classical completeness target was met in Cycle II, the research was concluded at that point. Based on these findings, it can be concluded that the use of the TaRL approach in instruction can enhance students’ mathematics learning outcomes.